Isan worldview in the Khon Kaen version of the ’Suriyawong’ literature - Premwit Jirasanyansakul; Kritsada Wongkhamchan, Ph.D; Pat Kotchapakdee, Ph.D (Utilitas Mathematica, 2025)
This study explores the Isan worldview as depicted in the Khon Kaen version of the Suriyawong literature, using the structural theories of Claude Lévi-Strauss and Vladimir Propp to analyze its narrative and cultural elements. The Isan worldview encompasses perspectives on social roles, nature, and the supernatural, reflecting the beliefs, values, and social structures of Isan society. The analysis under Lévi-Strauss's framework reveals binary oppositions that underline the values of honor, gender roles, respect for hierarchy, and the relationship between humans and the supernatural. Propp’s morphological approach further dissects the narrative roles, where characters embody specific functions such as heroes, villains, and helpers, each reinforcing cultural values through their journeys, trials, and moral decisions. This research is qualitative, utilizing a combination of literature review and field data from informants knowledgeable in Isan culture. The findings highlight the distinctive characteristics of Isan folk literature, particularly its focus on karmic law, respect for spiritual beliefs, and deep ties to nature. Suriyawong not only serves as a medium for entertainment but also conveys moral lessons central to Isan philosophy, emphasizing perseverance, loyalty, and the impact of one’s actions on fate. This study enhances the understanding of how traditional Isan narratives function as cultural artifacts, preserving and transmitting essential values across generations.